Universality of KPZ equation and renormalization techniques in interacting particle systems - Gonçalves, Patrícia (2010)
In these notes we use renormalization techniques to derive a second order Boltzmann-Gibbs Principle which allow us to characterize the equilibrium fluctuations of weakly asymmetric exclusion processes as within the KPZ universality class.